Sustainable Rural Development as an Educational Starting Point in General Grammar Schools in Slovenia - Konečnik Kotnik, Eva (Journal for Geography, 2009)
Education is a very important basis of sustainable development. That is why the selected learning objectives in the syllabus for geography in general grammar schools in Slovenia will be analysed within this contribution (general grammar school in Slovenia is a secondary school with a general-educational emphasis that does not provide vocational education, but prepares students aged 15 to 19 for further education at universities). We have selected learning objectives that relate to economic geography as a general geography topic, with special emphasis on learning objectives that refer to agriculture, rural areas and sustainable development. This contribution will present the results of generic comparative analysis of selected learning objectives in syllabi that were issued during the period since the emergence of Slovenia as an independent state (1992, 1998 and 2008). The results of the evaluation of quoted learning objectives from the viewpoint of social needs, educational guidelines and geographical science, as well as the results of the evaluation from the viewpoint of geography teachers in general grammar schools will also be examined. Educational problems associated with economic geography, sustainable development and rural areas will be highlighted accordingly.